Patient-reported outcomes after oesophagectomy in the multicentre LASER study. Issue 9 (11th May 2021) - Markar, S R; Sounderajah, V; Johar, A; Zaninotto, G; Castoro, C; Lagergren, P; Elliott, J A; Gisbertz, S S; Mariette, C; Alfieri, R; Huddy, J; Pinto, E; et al.
Abstract: Background: Data on the long-term symptom burden in patients surviving oesophageal cancer surgery are scarce. The aim of this study was to identify the most prevalent symptoms and their interactions with health-related quality of life. Methods: This was a cross-sectional cohort study of patients who underwent oesophageal cancer surgery in 20 European centres between 2010 and 2016. Patients had to be disease-free for at least 1 year. They were asked to complete a 28-symptom questionnaire at a single time point, at least 1 year after surgery. Principal component analysis was used to assess for clustering and association of symptoms. Risk factors associated with the development of severe symptoms were identified by multivariable logistic regression models. Results: Of 1081 invited patients, 876 (81.0 per cent) responded. Symptoms in the preceding 6 months associated with previous surgery were experienced by 586 patients (66.9 per cent). The most common severe symptoms included reduced energy or activity tolerance (30.7 per cent), feeling of early fullness after eating (30.0 per cent), tiredness (28.7 per cent), and heartburn/acid or bile regurgitation (19.6 per cent). Clustering analysis showed that symptoms clustered into six domains: lethargy, musculoskeletal pain, dumping, lower gastrointestinal symptoms, regurgitation/reflux, and swallowing/conduit problems; the latter two were the most closely associated. Surgical approach, neoadjuvant therapy, patient age, and sex were factors associated with severe symptoms. Conclusion: A long-term symptom burden is common after oesophageal cancer surgery. Abstract : The aim of this questionnaire study was to identify long-term symptoms that affect quality of life after oesophageal cancer surgery. Symptoms clustered into six domains: lethargy, musculoskeletal pain, dumping, lower gastrointestinal symptoms, regurgitation/reflux, and swallowing problems. This demonstrates a poorly appreciated long-term symptom burden.